Phosphodiesterase-4D Knockdown in the Prefrontal Cortex Alleviates Memory Deficits and Synaptic Failure in Mouse Model of Alzheimer’s Disease - Shi, Yongchuan; Lv, Jinpeng; Chen, Ling; Luo, Guojun; Tao, Mengjia; Pan, Jianchun; Hu, Xiaoxiong; Sheng, Jianwen; Zhang, Shanjin; Zhou, Min; Fan, Huizhen (Frontiers in Aging Neuroscience, 2021)
Phosphodiesterase 4 (PDE4) dependent cAMP signaling plays a crucial role in cognitive impairment associated with Alzheimer’s disease (AD). However, whether inhibition of PDE4 subtypes or their splice variants in the prefrontal cortex positively regulates synaptic plasticity and antioxidative stress, and reverse β-amyloid 1-42 (Aβ 1-42, Aβ42)-induced cognitive impairment still need clarified. The present study determined whether and how PDE4D knockdown by microinjection of lenti-PDE4D-miRNA into prefrontal cortex reversed Aβ 1-42-induced cognitive impairment in behavioral, neurochemical and molecular biology assays. The results suggested that PDE4D knockdown increased time to explore the novel object and decreased latency to leave the platform in novel object recognition and step-down passive avoidance tests. Further study suggested that PDE4D knockdown decreased the number of working memory errors in the eight-arm maze test. These effects were prevented by PKA inhibitor H89. The subsequent experiment suggested that inhibition of PDE4D in the prefrontal cortex rescued the long-term potentiation (LTP) and synaptic proteins’ expression; it also increased antioxidant response by increasing superoxide dismutase (SOD) and decreasing malondialdehyde (MDA) levels. PDE4D knockdown also increased phosphorylated cAMP response element-binding protein (pCREB), brain-derived neurotrophic factor (BNDF), and antiapoptotic proteins’ expression, i.e. the ratio of Bcl-2/ Bax, and decreased caspase 3 level in the prefrontal cortex. These findings extend the previous findings and support the hypothesis that RNA interference-mediated PDE4D knockdown in the prefrontal cortex ameliorated memory loss associated with synaptic failure in AD mouse model by its antioxidant, antiapoptotic and neuroprotective properties.